Research on biological nitroten fixation in the international agricultural research centers - Graham, Peter H. (International Center for Tropical Agriculture, 1982)
Five of the international agricultural research centers (IARC's) currently have research programs in the area of biological nitrogen (N2) fixation. This paper reviews the activities of the centers in this area and highlights common and distinctive features of the programs, as well as their links with BNF activities in national programs and developed country laboratories.